Dapagliflozin: an effective adjunctive treatment in type 1 diabetes. Issue 2 (June 2021) - Yadegarfar, Ghasem; Livingston, Mark; Cortes, Gabriela; Alshames, Ramadan; Leivesley, Kate; Metters, Ann; Horne, Linda; Steele, Tom; Heald, Adrian H.
Abstract : Introduction: Many people with type 1 diabetes (T1DM) continue to run high HbA1c levels with an associated elevated risk of cardiovascular events and increased mortality. We describe here how adjunctive prescription of an SGLT2 inhibitor has improved the glycaemic control of several people with T1DM, where the new technology has been intensively deployed. Methods: We report outcomes of six adults with T1DM who have been given dapagliflozin in East Cheshire, UK. Initiation was with education/support from the diabetes specialist nurses. All had an HbA1c of 70 mmol/mol (8.6%) or more before this was initiated. All had been monitoring glycemia with a FreeStyle Libre monitor for at least 6 months prior to this. Results: The age range was 30–68 years. The mean duration of T1DM was 23.3 ± 5.5 years. All were on a basal-bolus regime. Over a 6 month period, HbA1c fell from 78.5 mmol/mol (9.3%) to 55 mmol/mol (7.2%). The greatest reduction in HbA1c was 57 mmol/mol (7.4%). Analysis of the FreeStyle Libre blood glucose records showed that the proportion of blood glucose readings on target (4–10 mmol/L) increased from 33.1 to 65.2% with the addition of dapagliflozin(P = 0.007). The proportion of blood glucose readings above target (>10 mmol/L) decreased from 68.0 to 26.4%, 6 months after initiation of dapagliflozin (P = 0.005). There was no increase in symptomatic hypoglycemia. Conclusion: Dapagliflozin as adjunctive therapy to basal-bolus regime insulin in individuals with T1DM was well tolerated and improved glycemic control with no increase in hypoglycemia. We provide further evidence of the value of this intervention.